Sovereign Hedging from the Ottoman Lessons to the Global South’s Strategic Resilience - Kurniawan Arif Maspul; Aditia Nugraha; Hasbi Yusron (Indonesian Journal Publisher, 2025)
This paper develops a pluralistic framework for strategic resilience tailored to Global South states confronting great-power rivalry, cascading transnational shocks, and the erosion of multilateral governance. It employs a systematic literature review and a qualitative multi-method design incorporating historical analysis of Ottoman Arab integration and contemporary case studies of the South China Sea and the Russia–Ukraine war. The study synthesises theoretical insights from realism, liberal institutionalism, constructivism, post-colonial critique, and New Security Studies to forge an integrated analytic lens. Findings identify five interlocking policy pillars: strategic autonomy and defence self-reliance; economic and energy resilience; innovative, issue-based alliances and forums; inclusive peacebuilding and ethical security; and technological and normative innovation. Operational recommendations include regional security pilots, a Global South strategic reserves consortium, joint defence-production pacts, and sustained investment in diplomatic cadres and civil-society track-two networks. Priority areas emphasise sustainable defence practices, food and energy sovereignty, supply-chain diversification, and norm entrepreneurship linking disarmament, development finance, and digital governance. The approach explains how diverse hedging, institutional design, narrative construction, and local capacity-building can reduce dependency while maintaining cooperative diplomacy by combining historical parallels and modern empirical evidence; it offers an actionable policy blueprint enabling Global South actors to translate geopolitical disruptions into durable autonomy, equitable development and resilient peace. Recommendations require transparent governance, rigorous financing mechanisms, accountability metrics and sustained South-South partnerships for long-term strategic impact and moral legitimacy.